Immunohistochemical Localization of Collagen Types I, III, and IV, Laminin, Fibronectin, and Keratin in the Endolymphatic Sac - Harada, Teruhiko; Kim, Youngki; Juhn, Steven K.; Sakakura, Yasuo (Annals of Otology, Rhinology & Laryngology, 2000)
We have employed immunohistochemistry to obtain baseline information on the molecular constituents of the extracellular matrix (ECM) of the endolymphatic duct (ED) and endolymphatic sac (ES) of the chinchilla. The results demonstrated that collagen types I and III were distributed in the subepithelial layer in the ED and ES, type IV collagen and laminin in the basement membranes, and fibronectin in the subepithelial layer and partly in the conglomerated cells in the ES. Collagen type III was diffusely distributed in the whole subepithelial layer of the ES, whereas collagen type I was concentrated densely in the deep layer of the interstitium, although gradually, the cuboidal epithelium in the ES was transformed into a flatter type in the ED. The epithelial cells of the ED and ES were clearly positive for keratin. This study deals, in particular, with the normal distribution of ECM components of the ED and ES of the chinchilla.